DETERMINATION OF PHTHALATE ESTER COMPOUNDS IN SEMBRONG RIVER SEDIMENT - Muhamad, Aida; Abd. Karim, Ahmad Tarmizi; Zakaria, Nur Fathanah; Jonya Ak Rapok, Krystabel (Journal of Techno-Social, 2016)
River sediment contamination is a cause of decline in water quality which brings a detrimental effect on aquatic ecosystems and human life. The purpose of this study is to determine the existence and pollution level of PAEs compound in the Sembrong River sediments. Sembrong River was chosen because the river has been found to contain heavy metals and other pollutants according to previous studies. Sediment samples were collected using a core sediment sampler at 3 different locations along the river banks. Laboratory tests were conducted using GC-MS to determine the concentration of phthalate ester compounds in Sembrong River sediments. Results showed that the concentrations of PAEs are in the range of 0.01-15.63 mg/kg. Di-n-butyl phthalate (DBP), and di-(2-ethylhexyl) phthalate (DEHP) are the highest concentration of compounds found in the sediment. Other PAEs detected in the sediment of Sembrong River are dimethyl phthalate (DMP), diethyl phthalate (DEP), benzyl butyl phthalate (BBP), and di-n-octyl phthalate (DNOP).